Curbing Precariousness Facing Non-Standard Employees in the Private Security Industry: Employers’ Viewpoint - Bhebhe, Moment (African Journal of Employee Relations, 2022)
The pervasiveness of precariousness facing non-standard employees in Zimbabwe’s private security industry has for long become a major cause of concern, specifically as the global demand for decent employment is gaining momentum. This qualitative research study examined strategies applied by and challenges facing employers in curbing precariousness among the predominantly fixed-term contracted employees in the private security industry in Zimbabwe. The study involved 15 participants who were purposively identified from the Security Association of Zimbabwe, the largest employer association in the industry. A major finding of the study was that the nature of business service in the security industry led companies to engage personnel mostly on a fixed-term contractual type of employment. Such employment was found to be associated with poor and decimating conditions of work for the security personnel in the industry, and that much of their work life was enveloped in intense precariousness. The major impediments amplifying the failure to tackle employee precariousness in the security industry include the existence of fragmented relationships between two divergent employer associations in the industry, the prevalence of unregistered security firms, perceived improper regulation of the industry, and weakened employee representation by workers’ committees and trade unions operating in the industry. It is the study contention that the creation of an enabling environment to redress unfair and poor working conditions facing security guards is indispensable. Government lobbying to restructure the business regulatory framework is considered fundamental to the independent and autonomous functioning of the industry, and a precursor to tackling aggravated employee precariousness.